2019
DOI: 10.3390/cancers11091359
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric AKT Inhibitors Target Synthetic Lethal Vulnerabilities in E-Cadherin-Deficient Cells

Abstract: The CDH1 gene, encoding the cell adhesion protein E-cadherin, is one of the most frequently mutated genes in gastric cancer and inactivating germline CDH1 mutations are responsible for hereditary diffuse gastric cancer syndrome (HDGC). Using cell viability assays, we identified that breast (MCF10A) and gastric (NCI-N87) cells lacking CDH1 expression are more sensitive to allosteric AKT inhibitors than their CDH1-expressing isogenic counterparts. Apoptosis priming and total apoptosis assays in the isogenic MCF1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 53 publications
0
30
0
Order By: Relevance
“…All animal experiments were reviewed and approved by the University of Otago Animal Ethics Committee (AUP‐18‐226). Gastric organoids were generated from CD44 ‐Cre/ Cdh1 loxP/loxP / tdTomato mice as described previously [10,11]. In brief, organoids were generated from minced stomach tissue obtained from postnatal day 1 (D1) mice using an air–liquid interface and myofibroblast co‐culture.…”
Section: Methodsmentioning
confidence: 99%
“…All animal experiments were reviewed and approved by the University of Otago Animal Ethics Committee (AUP‐18‐226). Gastric organoids were generated from CD44 ‐Cre/ Cdh1 loxP/loxP / tdTomato mice as described previously [10,11]. In brief, organoids were generated from minced stomach tissue obtained from postnatal day 1 (D1) mice using an air–liquid interface and myofibroblast co‐culture.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, Bougen-Zhukov et al observed that AKT3 was upregulated in the majority of E-cadherin-deficient GCs, and mouse-derived gastric organoids lacking tumour suppressor gene CDH1 were sensitive to the apoptotic effects of miransertib. 82 This identification may be useful for providing new therapeutic strategies for hereditary and sporadic GC with mutations in the CDH1 gene, since germline truncation mutations in the CDH1 gene are found in 30%-50% families with hereditary diffuse GC. 83 Clinical perspective: resistance, toxicity and biomarkers The PI3K/AKT/mTOR pathway comprises a complex network of crosstalk with many parallel cascades, so its inhibition induces negative feedback resulting in activation of other compensatory signalling pathways.…”
Section: Uprosertib (Gsk2141795)mentioning
confidence: 99%
“…Interestingly, Bougen-Zhukov et al observed that AKT3 was upregulated in the majority of E-cadherin-deficient GCs, and mouse-derived gastric organoids lacking tumour suppressor gene CDH1 were sensitive to the apoptotic effects of miransertib. 82 This identification may be useful for providing new therapeutic strategies for hereditary and sporadic GC with mutations in the CDH1 gene, since germline truncation mutations in the CDH1 gene are found in 30%–50% families with hereditary diffuse GC. 83 …”
Section: Introductionmentioning
confidence: 99%
“…Li et al 21 reviewed and further supported promising molecular-targeted treatments with PI3K/mTOR inhibitors for patients with HDGC. Bougen-Zhukov et al 109 found that low levels of E-cadherin made breast (MCF10A) and gastric (NCI-N87) cancer cells more sensitive to allosteric AKT inhibitors than their isogenic wild-type counterparts. Two inhibitors preferentially inhibited the formation of gastric CDH1−/− organoids in mouse models, suggesting a survival benefit for patients with HDGC with CDH1 alterations.…”
Section: Introductionmentioning
confidence: 99%
“…Two inhibitors preferentially inhibited the formation of gastric CDH1−/− organoids in mouse models, suggesting a survival benefit for patients with HDGC with CDH1 alterations. 109 A new analysis by Beetham et al 110 identified novel synthetic lethal compounds as a new treatment or chemoprevention for E-cadherin-deficient cells via high-throughput screening. This new strategy confers an alternative preponderance on therapy that surpasses the current traditional drugs because it only targets defects in tumors with specific variants, not normal cells.…”
Section: Introductionmentioning
confidence: 99%